The Causal Relationship of the Success Factors of the Hotel Business Operations in Prachuap Khiri Khan District for Enhancing the Sports Tourism - Sangnin, Kittikun; Chalermpolyothin, Likita; Srichaiya, Usa (Dusit Thani College Journal, 2022)
This research aimed to study the success factors of the hotel business operation, and to analyze the causal relationship structure of the success factors of the hotel business operations to enhance sports tourism. The researcher chose a mixed research method; qualitative research used document research and In-depth interviews with 20 key informants; and quantitative research by survey data collection with questionnaires from hotel operators and executives in the area of ​​Prachuap Khiri Khan Province, a total of 281 people. This research used proportional stratified sampling method and specific sample selection; the research used tools including Semi-structured interview and questionnaire. The data were analyzed using a consensus dimensional distribution table, descriptive and inferential statistics using Linear Structure Relations program (LISREL). The results showed that 1) the developed causal relationship model was harmonious with the empirical data, with the values of ​​c2 = 88.93, df=34, p-value= 0.26, GFI= 0.97, AGFI= 0.92, CFI = 1.00, RMSEA = 0.02. The results found that the hotel's performance received the highest overall influence from the valued-sports innovation, followed by creative management, enhancing the services of sports and special events, upgrading the service innovation strategy, and fostering the learning organizations. The influence coefficients were 0.0.45, 0.25, 0.20, 0.18 and 0.10, respectively; there were 78% variables in the model that could explain the variance of the hotel's performance. The leaning organization received the highest overall influence from creative management with an influence coefficient of 0.95; the variables in the model accounted for 90% of the variance in the fostering the learning organizations. Moreover, the upgrading service innovation strategies received the highest overall influence from creative management with an influence coefficient of 0.90, the variables in the model accounted for 82 percent of the variance of upgrading service innovation strategies.